Medals by Stanislav Netљvolodov - Volkova, Uliana (project baikal, 2026)
The article deals with medals and plaquettes by architect and sculptor Stanislav Netšvolodov (born in 1935). Most of them are kept in the collection of the Pushkin State Museum of Fine Arts in Moscow. He struck and moulded more than 40 medals in 1980s. Sixteen medals are kept in the Pushkin Museum’s collection: most of them were donated or bought from the author.